In-vitro Antimicrobial Profiling and Standardization of a Classical Unani Polyherbal Formulation Targeting Uropathogens - Rahman, Khaleequr; Sultana, Arshiya (Current Traditional Medicine, 2026)
IntroductionA Polyherbal Unani Powder Formulation for Urinary Tract Infections (PUFP-UTI) comprises Adiantum capillus-veneris L., Cucumis sativus L., Lagenaria siceraria, Malva sylvestris L., and Portulaca oleracea L. This study aimed to evaluate the physicochemical characteristics, phytochemical composition, quantification of luteolin using HPLC, microbial safety, and in vitro antibacterial activity to assess the quality, efficacy, and safety of the formulation.MethodsPhysicochemical analysis included organoleptic properties, ash value, density, moisture content, and extractive values. Phytochemical screening detected phenols, tannins, flavonoids, alkaloids, glycosides, saponins, terpenoids, and sterols. Quantitative analysis measured total phenols, tannins, flavonoids, and alkaloids. Luteolin content was quantified by HPLC. Microbial contamination was assessed following WHO guidelines. Antibacterial activity was tested against E. coli, S. aureus, K. pneumoniae, E. faecalis, P. mirabilis, S. saprophyticus, and P. aeruginosa using the agar well diffusion method.ResultsPUFP-UTI exhibited acceptable physicochemical properties and contained significant amounts of phenols, tannins, flavonoids, alkaloids, and luteolin. The formulation met WHO safety standards for microbial contamination. It also showed substantial antibacterial activity against all tested pathogens. These results indicate that PUFP-UTI is a microbiologically safe herbal formulation with notable antimicrobial efficacy.DiscussionThe presence of multiple phytoconstituents, such as flavonoids and tannins, along with measurable luteolin content, may contribute to the observed antibacterial effect of PUFP-UTI. Its broad-spectrum activity against common uropathogens supports its pharmacological relevance. The formulation also complies with basic quality and safety benchmarks, reinforcing its potential as a safe traditional remedy.ConclusionPUFP-UTI's antibacterial properties support its traditional use in treating urinary tract infections. Further stability studies and clinical trials are recommended to confirm its therapeutic potential.
Keywords: standardization